Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I want to prove the following version of the Schwarz Inequality for complex numbers $a_1, a_2, \ldots, a_n \in \mathbb{C}$ and $b_1, b_2, \ldots, b_n \in \mathbb{C}$: $$|\sum_{j=1}^n a_j \overline{b_j}|^2 \leq \sum_{j=1}^n |a_j|^2 \sum_{j=1}^n |b_j|^2$$

Rudin has a nice proof where he shows that $$ \sum (|(\sum |b_j|^2)a_j - (\sum a_j \overline{b_j})b_j|^2) = (\sum |b_j|^2)(\sum |a_j|^2 \sum |b_j|^2 - |\sum a_j \overline{b_j}|^2) $$ Since the left side is $\geq 0$, so is the right side. If $b_1 = b_2 = \ldots = b_n = 0$, the Schwarz inequality is trivial; otherwise, we have $\sum |b_j|^2 > 0$, so that $(\sum |a_j|^2 \sum |b_j|^2 - |\sum a_j \overline{b_j}|^2) \geq 0$.

However, I don't find this proof very intuitive (how the heck did he come up with it?!), and I'd prefer to try it by induction: assume Schwarz holds for $n-1$, then show it's true for $n$. Is it possible to do it this way?

Here's what I have so far: Let $C = |\sum_{j=1}^{n-1} a_j \overline{b_j}|$. Then $$ |\sum_{j=1}^n a_j \overline{b_j}|^2 = |C + a_n \overline{b_n}|^2 = |C|^2 + 2|C||a_n \overline{b_n}| + |a_n \overline{b_n}|^2$$ Using the inductive hypothesis and some basic properties of the complex norm, we have $$ |\sum_{j=1}^n a_j \overline{b_j}|^2 \leq \sum_{j=1}^{n-1} |a_j|^2 \sum_{j=1}^{n-1} |b_j|^2 + 2|C||a_n||b_n| + |a_n|^2 |b_n|^2$$ We could use the triangle inequality to separate out that $|C|$ in the middle, but I don't think that helps...

share|cite|improve this question
See for a compilation of different proofs of the Cauchy-Schwarz inequality. Proof 6 is by induction. – Jeff Feb 2 '12 at 0:31
Cool! In Proof 6, they use the fact that $2 a_1 b_1 a_2 b_2 \leq a_1^2 b_2^2 + a_2^2 b_1^2$. Why is this true? – jamaicanworm Feb 2 '12 at 3:05
This is Young's inequality, which is very easy to prove. Noting that $0 \leq (a-b)^2 = a^2 + b^2 - 2ab$, you can rearrange to obtain $2ab \leq a^2 + b^2$. – Jeff Feb 2 '12 at 14:23
up vote 1 down vote accepted

Well, since no one gave a complete answer yet--and because I wrote one anyway--here's the proof by induction, in a manner which is hopefully easy for students (without much proof experience) to understand. Credit goes to the Wu and Wu paper posted by @Jeff.

Both sides of the Schwarz inequality are real numbers $\geq 0$. If $\sum_{j=1}^n |a_j|^2 \sum_{j=1}^n |b_j|^2 = 0$, then it must be that $a_1 = a_2 = \ldots = a_n = 0$ and/or $b_1 = b_2 = \ldots = b_n = 0$, so clearly $|\sum_{j=1}^n a_j \overline{b_j}|^2$ also $= 0$ and we are done. Now we only need to prove the case in which both sides of the inequality are positive.

Base Case. For $n = 1$, we have $$|\sum_{j=1}^1 a_j \overline{b_j}|^2 = |a_j \overline{b_j}|^2 = |a_j|^2 |b_j|^2 = \sum_{j=1}^1 |a_j|^2 \sum_{j=1}^1 |b_j|^2.$$

Inductive Step. The inductive hypothesis is $|\sum_{j=1}^{n-1} a_j \overline{b_j}|^2 \leq \sum_{j=1}^{n-1} |a_j|^2 \sum_{j=1}^{n-1} |b_j|^2$. Since we only need to worry about the case in which both sides are positive, so we can take the square root to obtain $$|\sum_{j=1}^{n-1} a_j \overline{b_j}| \leq \sqrt{\sum_{j=1}^{n-1} |a_j|^2 \sum_{j=1}^{n-1} |b_j|^2}.$$

Thus $|\sum_{j=1}^n a_j \overline{b_j}|$

$= |\sum_{j=1}^{n-1} a_j \overline{b_j} + a_n \overline{b_n}|$

$\leq |\sum_{j=1}^{n-1} a_j \overline{b_j}| + |a_n \overline{b_n}|$ (by the triangle inequality)

$\leq \sqrt{\sum_{j=1}^{n-1} |a_j|^2 \sum_{j=1}^{n-1} |b_j|^2} + |a_n \overline{b_n}|$ (by the inductive hypothesis)

$= \sqrt{\sum_{j=1}^{n-1} |a_j|^2} \sqrt{\sum_{j=1}^{n-1} |b_j|^2} + |a_n| |b_n|.$

Here we're a little stuck. We want to be able to square $|a_n|$ and $|b_n|$ and bring them into their respective square-rooted sums. So if we label $a = \sqrt{\sum_{j=1}^{n-1} |a_j|^2}$, $b = \sqrt{\sum_{j=1}^{n-1} |b_j|^2}$, $c = |a_n|$, and $d = |b_n|$, we want to be able to say $ab + cd \leq \sqrt{a^2 + c^2} \sqrt{b^2 + d^2}$. In fact, we can say it! This inequality is always true for any $a, b, c, d \in \mathbb{R}$, because

$0 \leq (ad - bc)^2 = a^2 d^2 - 2abcd + b^2 c^2$

$\Rightarrow 2abcd \leq a^2 d^2 + b^2 c^2$

$\Rightarrow a^2 b^2 + 2abcd + c^2 d^2 \leq a^2 b^2 + a^2 d^2 + b^2 c^2 + c^2 d^2$

$\Rightarrow (ab + cd)^2 \leq (a^2 + c^2)(b^2 + d^2),$

and since both sides are positive reals, we can take the square root.

We now use this inequality to obtain

$|\sum_{j=1}^n a_j \overline{b_j}| \leq \sqrt{\sum_{j=1}^{n-1} |a_j|^2} \sqrt{\sum_{j=1}^{n-1} |b_j|^2} + |a_n| |b_n|$

$\leq \sqrt{\sum_{j=1}^{n-1} |a_j|^2 + |a_n|^2} \sqrt{\sum_{j=1}^{n-1} |b_j|^2 + |b_n|^2}$

$= \sqrt{\sum_{j=1}^n |a_j|^2 \sum_{j=1}^n |b_j|^2},$

and just square both sides to complete the inductive step.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.